2015
DOI: 10.1371/journal.pone.0117458
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Function of CD4+ T Follicular Helper (Tfh) Cells Associated with Hepatocellular Carcinoma Progression

Abstract: Background and AimsCD4+ T follicular helper (Tfh) cells, a new subset of immune cells, have been demonstrated to be involved in the development and prognosis of tumors. However, their functional role in human hepatocellular carcinoma (HCC) is relatively unknown, and the detailed mechanisms in HCC development remain to be described.MethodsA total of 85 HCC patients with hepatitis B virus (HBV) infection, 25 HBV-relative liver cirrhosis (LC) patients, and 20 healthy controls (HC) were randomly enrolled. Flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 54 publications
(55 reference statements)
2
55
0
Order By: Relevance
“…Gu‐Trantien et al 25 found that when Tfh cell infiltration in breast cancer patients was greater, the prognosis of patients was better. Additionally, impaired function of Tfh cells is associated with hepatocellular carcinoma progression . Thus, Tfh cells are likely to be associated with prognosis of tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gu‐Trantien et al 25 found that when Tfh cell infiltration in breast cancer patients was greater, the prognosis of patients was better. Additionally, impaired function of Tfh cells is associated with hepatocellular carcinoma progression . Thus, Tfh cells are likely to be associated with prognosis of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, impaired function of Tfh cells is associated with hepatocellular carcinoma progression. 34,35 Thus, Tfh cells are likely to be associated with prognosis of tumor. Interestingly, in the present study, we found that the number of Tfh1 subtypes was negatively correlated with disease-free survival after tumor resection, which may be related to immunosuppression induced by high PD-1 expression in Tfh1 subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased proportion of CXCR5 + CD4 + Tfh cells was found to be associated with HCC disease progression. Furthermore, these cell types were found to have an attenuated function with reduced secretion of IL21, along with the inability to promote B cell maturation, and hence were suggested to be associated with low survival rates in HCC [41] .…”
Section: Nk Cellsmentioning
confidence: 99%
“…We read with great interest the article by Guo et al [1], which showed that increased percentage of circulating T follicular helper (cTFh) and circulating T follicular regulatory (cTFr) cells in non-small cell lung cancer (NSCLC) patients could be correlated with its pathogenesis. The role of TFh cells has been described in different types of cancers such as hepatocellular carcinoma [2] and breast cancer [3] and has also emerged as a key factor in the pathogenesis of viral-related diseases such as HBV [4].…”
Section: In Response To 'The Role Of Circulating T Follicular Helper mentioning
confidence: 99%